Evidence of the Zoonotic Transmission of Cryptosporidium among Children and Pets - Coelho, Natalia Marinho Dourado [UNESP]; Coelho, Willian Marinho Dourado; Gomes, Jancarlo Ferreira; Meireles, Marcelo Vasconcelos [UNESP]; Nagata, Walter Bertequini; de Lima, Valéria Marçal Felix [UNESP]; Santos-Doni, Thais Rabelo; Silva, Vitória Beatriz; da Silveira Neto, Luiz; Nakamura, Alex Akira [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (MDPI, 2023)
We investigated the zoonotic transmission of Cryptosporidium among the children (n = 188), dogs (n = 133), and cats (n = 55) living in 188 households. Fecal samples were examined using ELISA and confirmed via nested PCR. Coproantigens oocysts were detected in 3.7% of children, 8.3% of dogs, and 5.5% of cats. We found strong evidence of two cases of the zoonotic transmission of Cryptosporidium canis between children and dogs. Furthermore, four children and their respective pets (one dog and three cats) were infected with Cryptosporidium parvum, but we cannot exclude the hypotheses that the oocysts were transmitted from children to animals or that both hosts were infected by a shared source, such as contaminated water or food. The presence of an infected animal elevated the risk of zoonotic transmission by 129.7-fold (95% CI: 13.92-1209.68). Furthermore, sharing a bed with pets was identified as a risk factor for infection in children (OR: 9.9, 95% CI: 1.37-71.2). In conclusion, the zoonotic transmission of Cryptosporidium among children and pets cohabiting in the same household may be quite common, especially when infected animals lie or sleep on children's beds. These findings unequivocally highlight the public health concern surrounding C. canis.